Bicomponent composite electrochemical sensors for sustained monitoring of hydrogen peroxide in breast cancer cells. (1st December 2021) - Abdalla, Aya; Jones, Will; Flint, Melanie S.; Patel, Bhavik A.
Abstract: Hydrogen peroxide (H2 O2 ) is a molecule that plays an important role in cancer. Low concentrations in H2 O2 have an important physiological role in signalling whilst higher concentrations can induce cell death. Current sensors for cellular monitoring of H2 O2 are fragile and widely used for recording over a duration of minutes. Our study focused on developing a robust sensing device that can be used for sustained cellular monitoring of H2 O2 to provide vital insight into its role in cancer. We made composite electrodes using varying compositions of multiwall carbon nanotubes (MWCNTs) and platinum black (PtB). These electrodes were investigated using different electroanalytical approaches, scanning electron microscopy and energy dispersive X-ray spectroscopy. We found that a composition containing 15% MWCNT and 20% PtB was the most sensitive for H2 O2 detection. This electrode had a limit of detection of 17 nM and a sensitivity of 73.3 ± 1.1 A M −1 cm −2 when normalised for the conductive surface area. The composite electrode was able to provide stable current responses over 200 min. To evaluate the sensor, measurements in breast cancer cells were conducted, where administration of the pro-oxidant tert-Butyl hydroperoxide increased H2 O2 levels. This response was validated using a reactive oxygen species sensitive dye and confocal imaging. Our findings showcase that MWCNT PtB composite electrodes have excellent sensitivity and provide the ability to conduct sustained measurement. This approach towards sensor development can be suitable for monitoring different reactive species which are of paramount importance in complex biological environments.